Ag-nanowire films coated with ZnO nanoparticles as a transparent electrode for solar cell - COLEMAN, JONATHAN NESBIT (My University, 2011)
We demonstrate that solution-processible silver-nanowire films coated with zinc-oxide-nanoparticles (ZnO-NPs) can be used as transparent electrodes in organic photovoltaic devices. The ZnO-NP coating acts as electron extraction layer and as encapsulating agent, protecting the wires from oxidation and improving their mechanical stability. Scanning photocurrent microscopy showed photocurrent generation to be more efficient at the active material surrounding the wires. Ultra-violet illumination as present in the solar spectrum was found to enhance photocurrent by improving the ZnO in-layer conductivity through the photoconductive effect. Inverted polythiophene:fullerene devices using ZnO-NP coated silver-nanowires or indium-tin-oxide as transparent electrode reached power conversion efficiencies of 2.4%.
PUBLISHED
Keywords: Condensed matter physics; Organic photovoltaics